Compassionate Christ, Compassionate People: Liturgical Foundations of Christian Spirituality. By Bob Hurd. Collegeville, MN: Liturgical Press Academic, 2019. xi + 244 pages. $24.95 (paper). - Stoicoiu, Rodica M. M. (Horizons, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966920000353/resource/name/firstPage-S0360966920000353a.jpg